2016
DOI: 10.1155/2016/6397828
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Virtual Reality System Toyra on Upper Limb Function in People with Tetraplegia: A Pilot Randomized Clinical Trial

Abstract: The aim of this study was to investigate the effects of a virtual reality program combined with conventional therapy in upper limb function in people with tetraplegia and to provide data about patients' satisfaction with the virtual reality system. Thirty-one people with subacute complete cervical tetraplegia participated in the study. Experimental group received 15 sessions with Toyra® virtual reality system for 5 weeks, 30 minutes/day, 3 days/week in addition to conventional therapy, while control group only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 54 publications
1
85
1
Order By: Relevance
“…The findings of this study were consistent with those reported by Dimbwadyo et al [ 14 ] in 2016 that VR along with conventional therapy produces similar results in upper limb function when compared to only conventional therapy. In the present study, the small sample size (N=22) may have contributed to the absence of statistical significance between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study were consistent with those reported by Dimbwadyo et al [ 14 ] in 2016 that VR along with conventional therapy produces similar results in upper limb function when compared to only conventional therapy. In the present study, the small sample size (N=22) may have contributed to the absence of statistical significance between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…The participants in the EG used a controller in this study, but the study included both subjects with motor-complete and incomplete SCI, with the sum of ASIA-A and ASIA-B accounting for 7 (58%) of the 12 participants in the EG and 10 participants (70%) in the CG, respectively. In addition, the time from SCI onset to enrollment in the present study was about a month, while those in the studies by Dimbwadyo-Terre et al [14] and Prasad et al [15] ranged from 4 to 5 months and from 10 to 15 months, respectively. Previous research has shown that the potential for neurological recovery was greater in incomplete SCI than in complete SCI [16], motor recovery decreases 6 months after injury [17,18], early www.e-arm.org rehabilitation was effective, and the possibility of motor recovery was higher [19].…”
Section: Discussioncontrasting
confidence: 51%
“…Few studies have examined the VR methods in patients with SCI, and the findings of this study were inconsistent with previous studies. Dimbwadyo-Terrer et al [14] reported that VR combined with CR showed similar results with CR alone in patients with tetraplegia. Unlike our study, that of Dimbwadyo-Terrer et al [14] only targeted patients with motor-complete SCI (ASIA-A and ASIA-B), of which ASIA-A accounted for 11 (69%) of the 16 participants in the EG and 10 (67%) of the 15 in the CG.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies on the effect of VR in SCI have been limited; most of them emphasize the positive effects of VR on mood and the need for larger sample size in validating the author observations in this study. Randomized controlled studies on SCI in a small population were conducted by Dimbwadyo-Terrer et al [24] and Prasad et al [22] to determine the effects of VR in the upper limb function, which have shown that VR combined with the conventional therapy yield similar results as with the conventional therapy alone. In neurological conditions such as stroke, the evidence of VR effectiveness in systematic reviews was found to be of "low quality" [25], and in multiple sclerosis [26], VR was reported to be not significantly effective as compared to the conventional therapy.…”
Section: Discussionmentioning
confidence: 99%